High school teachers’ perceptions of the qualities of good citizenship in post-genocide Rwanda: A Q-methodological approach - Nzahabwanayo, Sylvestre (My University, 2018)
This study investigates high school teachers’ perceptions of the qualities of good citizenship in post-genocide Rwanda. It contributes to the existing literature around conceptions of good citizenship in conflict-affected contexts. The research engages with Q-Methodology conducted among a sample of 58 Rwandan high school teachers. It is revealed that the high school teachers cluster into four groups representing four perspectives about good citizenship. The first perspective describes good citizenship as being mindful or considerate of the 1994 genocide perpetrated against the Tutsi and promoting unity as well as reconciliation among Rwandans. Good citizenship is seen as avoiding any form of verbal/behavioral discrimination against victims of the genocide, and fighting divisionism, genocide ideology as well as hate speech. It also involves contributing towards programs meant for helping genocide orphans and widows to improve their lives. The second perspective, held by the majority of teachers, characterizes good citizenship as being morally upright and demonstrating a strong sense of patriotism. This account appears as the primary and dominant definition of good citizenship. The third perspective depicts good citizenship as being politically enthusiastic. For this group, good citizenship is perceived in terms of political literacy coupled with active political commitment. The fourth perspective conceives good citizenship in terms of promoting justice. Good citizenship is seen as denouncing what is wrong and fighting all forms of corruption, nepotism and discrimination. The study shows that the vast majority of teachers tend to associate good citizenship with good character and patriotism. A very limited number of teachers conceptualize good citizenship in terms of fighting injustices prevailing in society and participating actively in politics. Against such an imbalance, this study advocates a shift towards more critical forms of citizenship. It also argues for the reinforcement of democratic and participatory skills among teachers. This research argues that conceptions of good citizenship are context dependent. Hence, there is a need to broaden citizenship concepts.
A research submitted in partial fulfilment for the MA in Social and Psychological Research, October 2018